Investigation regarding the correlation of the relative influences during the extrusion process of cast films on the residual melt quality - Schöppner, Volker; Trienens, Dorte

Psychologie - Gretz, Daniela (Theodor-Fontane- Handbuch)

Rezeption zu Lebzeiten - Gretz, Daniela (Theodor- Fontane-Handbuch)

Beteiligung im Onlineunterricht in der Berufsfachschule. - Sommer, Sabrina; Förster, Anika (Therapie Lernen)

Schulkulturbezogene Schultypen im Zeitalter der digitalen Transformation. Eine Typologie unter Berücksichtigung von Hintergrundmerkmalen der zur Schulkultur befragten Lehrkräfte - Caruso, Carina; Drossel, Kerstin; Heldt, Melanie (MedienPädagogik)
In view of technological progress, a digitalisation deficit in German schools as well as the experiences in schools as a result of the Corona pandemic, it becomes apparent that the question of a school culture conducive to learning retains its relevance in the age of digital transformation: On the one hand, it is evident that school culture changes in view of the digital transformation. On the other hand, it contributes to the successful implementation of digital media. Previous research findings in connection with the digital transformation focus on particular competencies of teachers (Meyer, Becker, and Bock 2023; Caruso, Heldt, and Drossel 2022; Vogelsang et al. 2023) and their cooperative behaviour (Drossel and Heldt 2022; Schulze, Drossel, and Eickelmann 2022). These questions whether school culture-related school types can be identified or not and how teachers perceive the school culture have been less considered so far. This article is dedicated to this question and explores if the school culture-related school types differ in terms of the background characteristics of the teachers. Based on a Latent Class Analysis, three school culture-related school types become apparent: strong in innovation and cooperation (Type I: 45.74 %), highly innovative and inhibited cooperation (Type II: 17.95 %), inhibited in terms of innovation and cooperation (Type III: 36.31 %). The types do not differ from each other regarding the background characteristics.

Gemeindereferent_innen als Katalysator einer Transformation von Kirche? Professionsbezogene Perspektiven - Caruso, Carina; Hobelsberger, Hans (Gemeindereferent:in. Kompetenzen und Potenziale eines unterschäzten Berufs. Eine Studie zu Berufsbild und kirchlich-pastoraler Transformation)

Design und Ergebnisse des qualitativen Studienteils - Jung , Jennifer; Caruso, Carina (Gemeindereferent:in. Kompetenzen und Potenziale eines unterschätzten Berufs. Eine Studie zu Berufsbild und kirchlich-pastoraler Transformation)

Elisabetta Lupi, Jonathan Voges (Eds.), Luxus. Perspektiven von der Antike bis zur Neuzeit - Harnack, Maria

Forderer, Tanja, Was Gott zusammengefügt hat...? Eine argumentationsanalytische Untersuchung von Ehe-Scheidung im Neuen Testament am Beispiel von Mk 10,1–12 und 1Kor 7,10–16 - Breuer, Saskia Rebecca (Theologische Revue)

Einführung - Breuer, Saskia Rebecca; Paul, Clarissa; Schmidt, Eckart (Konflikte und Krisen im Neuen Testament und ihre Bewältigungsstrategien)